DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF GLICLAZIDE AND SITAGLIPTIN PHOSPHATE MONOHYDRATE IN BULK AND TABLET DOSAGE FORM - C. RUBINA REICHAL; M. GOPAL RAO (International Journal of Pharma and Bio Sciences, 2015)
The objective of this study was to develop a simple, specific, precise and accurate reverse phase high performance liquid chromatographic (RP-HPLC) method for the simultaneous estimation of Gliclazide (GLZ) and Sitagliptin Phosphate Monohydrate (SPM) in bulk and pharmaceutical dosage form. In the present work, SHIMADZU HPLC with UV detector LC 10AT VP with analytical column Phenomenex Luna (C18) A 100RP Column, 250mm x 4.6mm x 5µm, an injection volume of 20µl was injected and eluted with mobile phase Water: Acetonitrile (40:60) pumped at a flow rate of 1.0ml/min. Gliclazide (GLZ) and Sitagliptin Phosphate Monohydrate (SPM) were eluted at 3.268 and 2.260 min. The detection was carried out at a wavelength of 253nm. The method has shown good linearity in the concentration range of 5-25µg/ml for Gliclazide and 20-100µg/ml for Sitagliptin phosphate monohydrate with a correlation coefficient of (r2) 0.9997 and 0.9940. The percentage assay values were found to be 100.01 and 99.3 for Gliclazide (GLZ) and Sitagliptin Phosphate Monohydrate (SPM). Limit of detection and limit of quantification were found to be 0.4364µg/ml and 1.3232 µg/ml for Gliclazide, 0.6 -µg/ml and 1.9 µg/ml for Sitagliptin Phosphate Monohydrate respectively. The method was validated for system suitability, linearity, accuracy, precision, robustness and ruggedness of the sample solution.